(3GdeWGdH GdYdjI aj efGbH GdTGaYjIs - (3GdaGQhbj , YHO GdQMef Hf GdMSjf Hf YHO Gddg GdHcQj GdhGSWj,J (B776 (3g` s
(3ChdgG (B:s
(3CMeO Gddg Me GdTGcQjf s
(3BNQgG (B:s
(3JfJgi ai CKfGA JQLeI fLe GdOjf GdHGQRi s
(3hgh ai WHbGJ GdYdeGA GdTGaYjI ef GdeJbOejf hGdeJCNQjfhbO ChVM ai ebOeJg HjGf GdcJH GdJi CdaJ ai WHbGJ GdTGaYjI hefGbHge bHdgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B304s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B2 - (3U (B145 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
Keywords: (3GdJGQjNs